Antibacterial Activity of Endophytic Bacteria of Seagrass Symbiont Enhalus acoroides from Tiwoho Waters, North Minahasa - Purniasih, Ni Komang Pitri; Ginting, Elvy Like; Wullur, Stenly; Mangindaan, Remy E. P.; Rumampuk, Natalie D. C.; Pratasik, Silvester Benny (Jurnal Ilmiah Platax, 2022)
Nutrient-poor marine bacteria are often found to form a living mechanism by associating with other marine organisms such as seagrass Enhalus acoroides. Seagrass serves as a habitat for marine biota and is known to produce bioactive compounds. Endophytic and epiphytic microbes that are symbiotic in seagrass have the ability to produce bioactive compounds similar to the bioactive compounds produced by their host. Therefore, this study aimed to obtain isolates of symbiont bacteria and to test their antibacterial activity.  The symbiotic bacteria isolates were tested for their antibacterial activity using gram-negative bacteria such as E. coli and S. typhi, and gram-positive bacteria such as S. aureus and S. mutans. Antibacterial activity test was carried out using the paper disc method. Observation of antibacterial activity was carried out for 3x24 hours by observing the growth of the resulting inhibition zone. The zone of inhibition was measured to determine the diameter and strength of the bioactive compounds produced by symbiotic bacteria.A total of six isolates of symbiotic bacteria were obtained from the seagrass Enhalus acoroides with varied morphological characteristics. The six isolates of symbiont bacteria showed antibacterial activity and could inhibit and kill pathogenic bacteria. Two of the six isolates of symbiotic bacteria that produced the largest diameter of the inhibition zone were isolates E (Ep1) 3,5 mm and F (En3) 4 mm in S. mutans test bacteria.Keywords: Antibacterial, Isolation, Enhalus acoroides, Symbionts, Tiwoho AbstrakBakteri laut yang miskin nutrisi banyak dijumpai membentuk mekanisme hidup dengan cara berasosiasi dengan organisme laut lainnya seperti lamun Enhalus acoroides. Lamun berfungsi sebagai habitat biota laut dan diketahui dapat menghasilkan senyawa bioaktif. Mikroba endofit dan epifit yang bersimbiosis pada lamun mempunyai kemampuan untuk memproduksi senyawa-senyawa bioaktif yang serupa dengan senyawa bioaktif yang diproduksi inangnya. Oleh karena itu, penelitian ini bertujuan untuk mendapatkan isolat bakteri simbion serta menguji aktivitas antibakterinya.  Isolat bakteri simbion diuji aktivitas antibakterinya menggunakan bakteri uji gram negatif seperti E. coli dan S. typhi, dan bakteri uji gram positif seperti S. aureus dan S. mutans. Uji aktivitas antibakteri dilakukan menggunakan metode kertas cakram. Pengamatan aktivitas antibakteri dilakukan selama 3x24 jam dengan mengamati pertumbuhan zona hambat yang dihasilkan. Zona hambat diukur untuk mengetahui diameter dan kekuatan senyawa bioaktif yang dihasilkan oleh bakteri simbion.  Sebanyak enam isolat bakteri simbion yang didapatkan dari lamun Enhalus acoroides dengan karakteristik morfologi yang bevariasi. Keenam isolat bakteri simbion menunjukkan adanya aktivitas antibakteri dan dapat menghambat serta membunuh bakteri pathogen. Dua dari enam isolat bakteri simbion menghasilkan diameter zona hambat terbesar adalah isolat E (Ep1) 3,5 mm dan F (En3) 4 mm pada pada bakteri uji S. mutans.Kata kunci: Antibakteri, Isolasi, Enhalus acoroides, Simbion, Tiwoho